Efficacy and safety of blinatumomab in Chinese patients with relapsed/refractory B-cell acute lymphoblastic leukemia: a single-center retrospective study - Wang, Yan; Chang, Chun; Wang, Zhen; Zhao, Jie; Wang, Jingbo (Frontiers in Oncology, 2025)
BackgroundBlinatumomab is a bispecific T-cell engager approved for the treatment of relapse/refractory B-cell acute lymphoblastic leukemia (R/R B-ALL). Most studies evaluating blinatumomab were conducted in Caucasian populations, with limited data available in Chinese patients. This retrospective study aims to evaluate the efficacy and safety of blinatumomab in Chinese patients with R/R B-ALL.MethodsA total of 19 patients (10 males, 9 females) with a median age of 49 years (range: 9-66) who received blinatumomab treatment at the Aerospace Center Hospital between November 2021 and November 2024 were included. Rates of complete remission (CR) and minimal residual disease (MRD) response, 1-year overall survival (OS) and relapse-free survival (RFS), and adverse events were analyzed.ResultsThe median number of blinatumomab cycles administered was 1 (range: 1-6). Twelve (80.0%, 95% confidence interval [CI]: 51.9-95.7) of the 15 patients with overt marrow disease achieved CR, with 8 achieving MRD negativity. Four patients with < 5% blast but positive MRD all sustained CR and achieved MRD negativity. The overall MRD response rate was 63.2% (12/19, 95%CI: 38.4-83.7). The 1-year overall survival (OS) and relapse-free survival (RFS) rates were 64.2% ± 12.1% and 73.3% ± 11.4%, respectively. MRD responders had significantly better OS compared to MRD non-responders (log-rank test, P = 0.023). Of the 16 patients with CR, 62.5% proceeded to allogeneic hematopoietic stem cell transplantation (allo-HSCT). The most frequent adverse event was cytokine release syndrome, which occurred in 11 patients (10 with grade 1–2 and 1 with grade 3 severity).ConclusionBlinatumomab is both effective and well-tolerated in Chinese patients with R/R B-ALL, achieving high rates of CR and MRD negativity and facilitating more patients’ eligibility for allo-HSCT.